Association of sex and height with a lower ankle brachial index in the general population. (December 2018) - Kapoor, Ridhima; Ayers, Colby; Visotcky, Alexis; Mason, Peter; Kulinski, Jacquelyn
The ankle–brachial index (ABI) is a predictor of cardiovascular events, mortality and functional status. Some studies have noted a higher prevalence of peripheral artery disease in females compared to males. Differences in height might account for these observed sex differences, but findings are conflicting. The 2003–2004 National Health and Nutrition Examination Survey (NHANES) cohort includes participants from 15 geographic locations, selected annually to represent the general population. Sample-weighted multivariable linear and logistic regression modeling was performed with ABI as the dependent variable and height and sex as primary exposure variables of interest. There were 3052 participants with ABI data (mean age 57 years, 51% female). The mean (±SE) ABI was 1.09 (±0.006) and 1.13 (±0.005) for females and males, respectively ( p < 0.0001). Shorter height was associated with a low ABI (OR 0.91 per 4 cm, 95% CI: 0.86–0.96; p =0.001). In a fully adjusted model, female sex was associated with a low ABI (OR 1.34, 95% CI: 1.04–1.72; p =0.025) independent of height and traditional cardiovascular disease (CVD) risk factors. Age, diabetes, tobacco use, known CVD, hypertension and race were associated with a low ABI (all p < 0.001). The ABI was 0.03 lower in females than in males in the general population and in a healthy cohort. Lower ABI values in healthy females do not appear to be due to occult vascular disease but rather a normal phenomenon with some contribution from height. Therefore, population sex-specific ABI thresholds should be utilized in the diagnosis of peripheral artery disease to account for these intrinsic differences.